Edukasi gizi seimbang: Gerakan cegah stunting (GEGATI) - Apdola, Zikrina; Anggraini, Anggraini; Rachmawati, Fijri; Fratama, Aldy; Putri, Miranda (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Stunting is the stunted growth and development of children due to chronic malnutrition. This is characterized by a child's height not meeting standards, especially during the first 1,000 days of life. In Banjar Masin Village, several children fall into the malnourished category. Purpose: To provide knowledge to expectant mothers and mothers with toddlers regarding stunting, its management and prevention, and the importance of balanced nutrition for child growth and development. Method: The GEGATI